Modulation of Leukocyte Subsets Mobilization in Response to Exercise by Water Immersion Recovery - Ottone, Vinícius de Oliveira; De Paula, Fabrício; Brozinga, Paula Fernandes Aguiar; Matos, Mariana Aguiar de; Duarte, Tamiris Campos; Costa, Karine Beatriz; Garcia, Bruna Caroline Chaves; Silva, Thyago José; Magalhães, Flavio De Castro; Coimbra, Cândido Celso; Esteves, Elizabethe Adriana; Pinto, Kelerson Mauro de Castro; et al. (Frontiers in Physiology, 2022)
Purpose: To investigate the effect of different water immersion temperatures on the kinetics of blood markers of skeletal muscle damage and the main leukocyte subpopulations. Methods: Eleven recreationally trained young men participated in four experimental sessions consisting of unilateral eccentric knee flexion and 90 min of treadmill running at 70% of peak oxygen uptake, followed by 15 min of water immersion recovery at 15°C, 28°C or 38°C. In the control condition participants remained seated at room temperature. Four hours after exercise recovery, participants completed a performance test. Blood samples were obtained before and immediately after exercise, after immersion, immediately before and after the performance test and 24 hours after exercise. The number of leukocyte populations and the percentage of lymphocyte and monocytes subsets, as well as the serum activity of creatine kinase and aspartate aminotransferase were determined. Results: Leukocytosis and increase in blood markers of skeletal muscle damage were observed after the exercise. Magnitude effect analysis indicated that post-exercise hot-water immersion likely reduced the exercise-induced lymphocytosis and monocytosis. Despite reduced monocyte count, recovery by 38oC immersion, as well as 28oC, likely increased the percentage of non-classical monocytes in the blood. The percentage of CD25+ cells in the CD4 T cell subpopulation was possibly lower after immersion in water at 28 and 15oC. No effect of recovery by water immersion was observed for serum levels of creatine kinase and aspartate aminotransferase. Conclusions: Recovery by hot-water immersion likely attenuated the leukocytosis and increased the mobilization of non-classical monocytes induced by a single session of exercise combining resistance and endurance exercises, despite no effect of water immersion on markers of skeletal muscle damage. The monocyte response mediated by hot water immersion may lead to the improvement of the inflammatory response evoked by exercise in the skeletal muscle.